Germinated Brown Rice Preparation for Value Added Material for Healthy Brewed Vinegar - Wiramsri Sriphochanart; Warawut Krusong; Utoomporn Surayot; Orachorn Mekkerdchoo; Pongsert Sriprom (My University, 2021)
Soaking grains in water during the preparation of germinated brown rice (GBR) can result in the multiplication of bacterial contaminants. To address this problem, a system was designed to automatically change the soaking water every 6 h. A significant reduction of the contaminants was observed. GBR was saccharified by mold bran Amylomyces rouxii. The 5 day saccharified GBR that contained the highest -amylase and glucoamylase activities was further used for alcohol fermentation by yeast Saccharomyces cerevisiae. Then, acetic acid was produced by Acetobacter aceti through a semi-continuous process. In the evaluation of the nutritional quality during processing, significant increments in the levels of -aminobutyric acid (GABA), antioxidant activities (DPPH), and total phenolic contents were found during soaking, but these levels progressively decreased in wine and were lowest in vinegar. Moreover, the soaking period from 36 h to 48 h had no significant effect on these substances. GC-MS analysis indicated that four important volatile organic compounds in the produced wine and vinegar were reported for their antimicrobial activity. Furthermore, no change in GABA was found in the vinegar over 6 months of storage. Thus, using this method could successfully produce brewed vinegar with health benefits from GBR.
Keywords: Brown rice; Mashing; Acetic acid bacteria; GABA and Rice Research